2020
DOI: 10.1016/j.toxrep.2020.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Comparative and cumulative quantitative risk assessments on a novel heated tobacco product versus the 3R4F reference cigarette

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In general, the common pollutants released by cigarettes are highly similar to 3R4F, followed by HTPs, and ecigarettes have the lowest similarity. Note: The unit (ug/mL) represents the concentration of the common pollutants per millilitre of aerosol; "ND" represents not detected; " a " and " b "represents the concentration of the common pollutants released from 3R4F according to the research by Hirn and Marcilla et al [21,47].…”
Section: Comparative Analysis Of Common Pollutants Released From Different Types Of Tobacco Products and 3r4fmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, the common pollutants released by cigarettes are highly similar to 3R4F, followed by HTPs, and ecigarettes have the lowest similarity. Note: The unit (ug/mL) represents the concentration of the common pollutants per millilitre of aerosol; "ND" represents not detected; " a " and " b "represents the concentration of the common pollutants released from 3R4F according to the research by Hirn and Marcilla et al [21,47].…”
Section: Comparative Analysis Of Common Pollutants Released From Different Types Of Tobacco Products and 3r4fmentioning
confidence: 99%
“…Forster et al compared the levels of potentially harmful constituents (HPHCs) in mainstream emissions from IQOS and Glo (two typical HTPs) [16][17][18][19]. Current studies have mostly relied on smoking machines to complete the smoking experiment [2,9,14,20,21], but machine smoking does not necessarily reflect how people actually use the products [22]. Different researchers have used different smoking protocols to answer different questions and have shown that more intense smoking leads to higher yields of smoke-related chemicals [20,21].…”
Section: Introduction 1backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the approach evaluating combined exposure to multiple compounds in the emissions of TRP and other complex mixtures is essentially the same as one of the methods described by EFSA (i.e., dose addition), the health impact evaluation of tobacco products differs from the usual goal of risk assessment: it aims to evaluate harm reduction claims and to quantify the change in cumulative exposure. For the assessment of the complex mixtures in cigarette or TRP emissions, various concepts have been proposed, ranging from the hazard index (HI) approach [ 42 ] or the RPF approach [ 12 ], to in vitro or in vivo whole mixture studies [ 27 , 43 , 44 ]. More pragmatic approaches to evaluating combined exposure to multiple chemicals are the Mixture Assessment Factor (MAF), as discussed in the context of REACH [ 45 ], or the threshold of toxicological concern (TTC) approach [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a daily consumer of loose snuff will ingest 15 micrograms/day after 2016, but ingested higher amounts earlier [ 35 ]. For comparison, TSNAs from a pack of low-tar cigarettes causes an exposure of 5 micrograms [ 36 ]. Thus, an average loose snuff user is currently exposed to 3 times higher levels to TSNAs than a pack-a-day smoker, and the difference was higher earlier [ 35 ].…”
Section: Discussionmentioning
confidence: 99%